Electronic properties of interfaces between N-Heterotriangulene donors and strong tetracyanoquinodimethane acceptors - Ajdari, Mohsen; Pappenberger, Ronja; Walla, Christian; Michalsky, Ina; Maaß, Friedrich; Kivala, Milan; Dreuw, Andreas; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2024)
N-Heterotriangulenes (N-HTAs) represent a class of functional molecules with high potential for optoelectronic materials, for example, as electron donating compounds in donor/acceptor (D/A) systems. The capability of two different N-HTAs, N-HTA 550 and N-HTA 557, the latter containing an additional 7-membered ring, to act as electron donors at interfaces with strong tetracyanoquinodimethane (TCNQ and F4TCNQ) acceptors is studied using high-resolution electron energy loss spectroscopy in combination with state-of-the-art quantum chemical calculations. For TCNQ/N-HTA bilayer systems adsorbed on Au(111), low-energy (<2.5 eV) electronic transitions which are attributed to charge transfer (CT) states for all four D/A combinations are identified. Based on substantial quantum chemical calculations, a generation of ground state CT complexes is excluded. Instead, CT in the excited state, in which an electron-stimulated CT from the N-HTAs to TCNQs is the underlying process, is proposed. The energies of the CT states are determined by the values of the ionization potential and electron affinity of the involved donor and acceptor.